The effects of ultrasonic waves and temperature on the extraction of lignin from rice straw in the presence of KOH - Martin, Timothy John Chan (2010)
The effects of ultrasonic waves and solution temperature on the extraction of lignin from rice straw (Oryzae sativa) in the presence of 1M KOH were studied for this experiment. Lignin is a component in rice straw that hinders the conversion of cellulose to sugars. These sugars could then used to convert as a biofuel. Alkalai extraction acts as a pretereatment process which dissolve lignin and hemicellulose in rice straw while leaving cellulose intact. Ultrasonic exposure based on several studies of other lignocellulose material was found to increase both lignin and hemicellulose removal. Different exposure times to ultrasonic waves were compared: 0, 5, 10, 15, 20, 25, 30, 35 minutes. Different initial solution temperatures for these eight samples were undertaken from 60, 70 and 80°C. Based on samples without ultrasonic assistance: 40.81%, 36.52%, and 50.56% of lignin were removed at 60°C, 70°C and 80°C respectively. Optimum exposure time was 20 minutes with lignin removals of 45.69%, 56% and 61.32% at solution tempearature of 60°C, 70°C and 80°C respectively Ultrasonic time and temperature were both found to have significant effect on lignin removal. Based on the analysis of the final dried residue, there were also some indications that cellulose exhibited some degradation.